2006
DOI: 10.1021/ef050267p
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Surfaces for Heavy Oil Pipelines To Inhibit Wax Deposition:  PP, EVA28, and HDPE

Abstract: Pipelines for heavy crude oils have recurrent clogging situations due to paraffin deposition that may lower production rates and be responsible for leakages. This work evaluates the effect of three polymers on crude oil wettability and on paraffin deposition inhibition: polypropylene (PP), high-density polyethylene (HDPE), and a vinyl acetate copolymer with 28% oxygen content (EVA28). Under static conditions, the interfacial tension between the crude oil and the linings was determined by the contact angle bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 32 publications
2
29
0
Order By: Relevance
“…In order to meet the actual working conditions in crude oil transportation, Quintella et al evaluated the influence of the flow state of crude oil on the inhibition of paraffin deposition when using three types of polymer coatings (Quintella et al 2006). Figure 1 shows the structures of three coatings: polypropylene (PP), high-density polyethylene (HDPE) and ethylene vinyl acetate copolymer (EVA28) with an oxygen content of 28%.…”
Section: Low Surface Energy Coatingsmentioning
confidence: 99%
“…In order to meet the actual working conditions in crude oil transportation, Quintella et al evaluated the influence of the flow state of crude oil on the inhibition of paraffin deposition when using three types of polymer coatings (Quintella et al 2006). Figure 1 shows the structures of three coatings: polypropylene (PP), high-density polyethylene (HDPE) and ethylene vinyl acetate copolymer (EVA28) with an oxygen content of 28%.…”
Section: Low Surface Energy Coatingsmentioning
confidence: 99%
“…Many early studies demonstrate surface energy and roughness as co-dependent factors in paraffin adhesion [168,172,173]. Quintella et al [174] showed the dependence of wax deposition on the contact angle of a surface with paraffin oil. They observed high wax deposition rates for vinyl acetate copolymers with 28% oxygen content (EVA28) when compared with the more hydrophobic polymers, polypropylene (PP) and high-density polyethylene.…”
Section: Paraffins and Wax Depositionmentioning
confidence: 99%
“…The laser beam is modulated by a chopper at a frequency of 10 Hz, and the signal magnitude is experimentally determined by a lock-in that sends the information to a dataacquisition interface. In this work the sample has not only a single known chromophore and the intrinsic fluorescence is being detected due to several chemical species of oil which are usually polycyclic aromatic hydrocarbons [31]. Thus, there's not a single a, since the signal registered by the detection system is the result of contributions of different chemical species, with specific electronic structures.…”
Section: Tlsmentioning
confidence: 99%